A combined goal programming and inverse DEA method for target setting in mergers. (January 2019) - Amin, Gholam R.; Al-Muharrami, Saeed; Toloo, Mehdi
Highlights: A new method for target setting in mergers is proposed. The method combines goal programming and inverse data envelopment analysis. The method allows decision makers to save desired resources. An application in banking sector is proposed. Abstract: This paper suggests a novel method to deal with target setting in mergers using goal programming (GP) and inverse data envelopment analysis (InvDEA). A conventional DEA model obtains the relative efficiency of decision making units (DMUs) given multiple inputs and multiple outputs for each DMU. However, the InvDEA aims to identify the quantities of inputs and outputs when efficiency score is given as a target. This study provides an effective method that allows decision makers to incorporate their preference in target setting of a merger for saving specific input(s) or producing certain output(s) as much as possible. The proposed method is validated through an illustrative application in banking industry.